Pembiayaan Murabahah dan Musyarakah Serta Pengaruhnya Terhadap Tingkat Likuiditas Pada Bank Umum Syariah - Iis Komalasari (Papanda Publisher, 2022)
This study aims to determine the effect of murabahah and musyarakah financing on liquidity in Islamic General Banking in Indonesia in 2013-2014. This research is a verification descriptive research using a quantitative approach. The data analysis method used multiple linear regression. The population in this study is Islamic General Banking in Indonesia for the period 2013-2017. By using purposive sampling. The sample used in this study amounted to 8 banks multiplied by 5 years of observation to 40 data as research samples. The analytical methods used are the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The results of the descriptive analysis show that murabaha financing, musyarakah financing and liquidity are low. Partially and simultaneously both show that murabahah and musyarakah financing have an effect on liquidity.